PENGEMBANGAN LKPD BERBASIS REALISTIC MATHEMATICS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Safitri, Noviana; Sari, Raras Kartika (Universitas Insan Budi Utomo, 2025)
The purpose of this exploration is to design a Student Worksheet (LKPD) that focuses on realistic mathematics on the topic of Function, with the aim of improving students' creativity potential, so that students can better understand and understand how to determine functions related to daily activities. This research method adopts the Research and Development (R&D) approach with the ADDIE model through five stages, namely analysis, design, development, implementation, and evaluation. The research subjects were 30 student respondents to be tested in large groups and 15 student respondents to be tested in small groups by implementing the 2024/2025 independent curriculum. Data collection in the study included questionnaires, tests, and documentation as well as expert assessment questionnaires to assess product validity, and student response questionnaires to assess the practicality of the products used and measure the accuracy of the effectiveness of the refined products. The validation process was carried out by media, material, and language experts. Product testing was carried out inviting student responses to the use of the product and the results of the evaluation of creative thinking skills which included indicators of initiation, fluency, originality, and elaboration. The results of the study showed that the products made had high validity, with an average percentage reaching 90% where all were included in the very accurate category, practicality was assessed as very good showing an average value of 100 from the student response questionnaire. Meanwhile, the results of the students' creative thinking ability test showed an average value of 100, which was included in the